PELATIHAN SWOT BALANCED SCORECARD UNTUK PENGUKURAN KINERJA INDUSTRI BRIKET ARANG - MARGARITA EKADJAJA; Tara Clarissa Djaja (Jurnal Bakti Masyarakat Indonesia, 2022)
The PKM team collaborated with Trinity Charcoal Indonesia which is a producer of charcoal briquettes in measuringperformance using the SWOT balanced scorecard method. The background of implementation of PKM activities is thepartner's expectation to increase profits to grow the company, because the increase in sales achieved by partner is notfollowed by the expected increase in profits. PKM activities help partners take advantage of their strengths, weaknesses,opportunities, and threats in determining business strategies so as to create a balance between various perspectives andthus partners can focus more on the target market to be served. The initial stage of implementing PKM was the teamconducted a webinar using the Zoom application with the topic of using the balanced scorecard for performancemeasurement. The success of the webinar implementation is evaluated through the partner's ability to create a balancedscorecard related to its business activities. The next step is the PKM team helps partners create a SWOT matrix.Information and data collection such as financial plans, marketing plans, operation plans, quality improvementprograms, and customer analysis related to partners is carried out by interviewing techniques through the WhatsAppapplication. Meanwhile, data collection of information related to partner industries is carried out through aquestionnaire technique distributed online through the google form. Based on the results of the measurement of the totalscore of the SWOT matrix, partners are in quadrant 1 position, which means partners can take advantage of the strengthsand opportunities of the products they produce. The results of the SWOT analysis prioritize partners' work plans in orderto improve their performance. The mandatory outputs for the implementation of PKM are published through the SERINAand Tarumanagara University online mass media. ABSTRAK Tim PKM bekerjasama dengan Trinity Charcoal Indonesia yang merupakan produsen briket arang dalam mengukurkinerja menggunakan metode SWOT balanced scorecard. Hal yang mendasari pelaksanaan kegiatan PKM adalah mitraberkeinginan meningkatkan keuntungan sehingga perusahaannya dapat berkembang, namun peningkatan penjualanproduk mitra tidak diikuti dengan peningkatan keuntungan yang diharapkan. Kegiatan PKM membantu mitramemanfaatkan strengths, weaknesses, opportunities, dan threats yang dimiliki dalam penentuan strategi bisnis sehinggatercipta keseimbangan antar berbagai perspektif dan mitra dapat lebih memfokuskan target market yang akan dilayani.Tahap awal pelaksanaan PKM adalah tim melaksanakan webinar menggunakan aplikasi Zoom dengan topik pemanfaatanbalanced scorecard untuk pengukuran kinerja. Keberhasilan pelaksanaan webinar dievaluasi melalui kemampuan mitradalam membuat balanced scorecard terkait dengan kegiatan usahanya. Tahap selanjutnya, tim PKM membantu mitramembuat matriks SWOT. Pengumpulan data informasi seperti mengenai rencana keuangan, rencana pemasaran, rencanapengoperasian, program peningkatan kualitas, dan analisa pelanggan terkait dengan mitra dilakukan dengan teknikwawancara melalui aplikasi WhatsApp. Sedangkan pengumpulan data informasi terkait dengan industri mitra dilakukanmelalui teknik kuesioner yang disebar secara online melalui google form. Berdasarkan hasil pengukuran total skormatriks SWOT, mitra berada pada posisi kuadran 1 yang berarti mitra dapat memanfaatkan kekuatan dan peluang dariproduk yang dihasilkannya. Hasil analisa SWOT tersebut memprioritaskan rencana kerja mitra agar dapat meningkatkankinerjanya. Luaran wajib pelaksanaan PKM dipublikasikan melalui SERINA sebagai luaran wajib dan media massaonline Universitas Tarumanagara sebagai luaran tambahan.